+0  
 
0
63
2
avatar

i really really need help plz can anybbody help due tommmorow

 Feb 22, 2022
 #1
avatar+675 
0

(a)

 

Because the curve C in Figure 3 crosses the x-axis at points A and B, the solutions of the equation are A and B:

 

y = x(x + 4)(x - 2)

0 = x(x + 4)(x - 2) ...


now solve for x -> x1 = 0, x2 = -4 and x3 = 2

 

We already know A or B are not zero,

 

so A = -4 (because A is negative) and B = 2 (because B is positive).

 Feb 23, 2022
edited by Straight  Feb 23, 2022
edited by Straight  Feb 23, 2022
 #2
avatar+675 
0

(b)

 

y = x(x + 4)(x - 2)    | distribute

y = x(x2 - 2x + 4x - 8)

y = x(x2 + 2x - 8)      | distribute

y = x3 + 2x2 - 8x

 

now use integration

 

\(\int (x^3+2x^2-8x)dx\)

 

now do it yourself.

 Feb 23, 2022

6 Online Users